2006
DOI: 10.3126/jiaas.v27i0.693
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Different Rice Lines Against Leaf and Neck Blast under Field Condition Of Chitwan Valley

Abstract: The severity of the rice blast disease (Pyricularia grisea) of both leaf and neck varies with different environment and it becomes destructive under favorable condition. The leaf and neck blast resistance and susceptible interaction of 30 different tropical rice lines were evaluated under low-, mid-and up-land conditions of Chitwan district and classified on the basis of disease severity with respect to susceptible check, Masuli. Of them, 5, 10, 12 and 3 rice lines were resistant to leaf blast, moderately resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…Similarly in this study significantly high mean blast incidence and severity were observed in rice fields at the booting and grain filling stage than at the vegetative and pre-anthesis stage. This was congruent with observation in other similar studies elsewhere (Puri et al, 2006;Ramappa et al, 2002). Comparable to a study reported by Asfaha, Selvaraj, and Woldeab (2015), at higher altitude blast incidence and severity were lower probably due to low relative humidity that hinders the development of the disease, while at a lower altitude, the temperatures were high and therefore not favorable for spore germination.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly in this study significantly high mean blast incidence and severity were observed in rice fields at the booting and grain filling stage than at the vegetative and pre-anthesis stage. This was congruent with observation in other similar studies elsewhere (Puri et al, 2006;Ramappa et al, 2002). Comparable to a study reported by Asfaha, Selvaraj, and Woldeab (2015), at higher altitude blast incidence and severity were lower probably due to low relative humidity that hinders the development of the disease, while at a lower altitude, the temperatures were high and therefore not favorable for spore germination.…”
Section: Discussionsupporting
confidence: 94%
“…However, the spores/conidia are efficiently moved from crop-to-crop and field-to-field by wind, and rain-water as well as the movement and accumulation of infected crop residues (Raveloson, Ratsimiala Romanta, Tharreau, & Sester, 2018). Though infection occurs at all stages of growth, infection at an early vegetative stage for foliar blast and at booting for neck blast is critical on the crop yield (Puri, Shrestha, Joshi, & Chhetri, 2006;Ramappa, Ravishankar, & Prakash, 2002). Early and severe infection causes stunting, development of small panicles, and a white-head often mistaken for insect pest damage (Mousanejad et al, 2010;Bonman, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance and susceptible interaction on rice conferred by single amino acid substitution in Pi-ta leucine rich domain (LRD) or in the AVR-Pi-ta176 protease motif that result in loss of resistant in plant and also disturb the physical interaction among them was reported by Jia et al (2000).Thus, the rice genotypes used in this study having different genetic background showed different interaction to leaf blast. Such result was also supported by the work of Koh et al (1987), Chaudhary (2001) and Puri et al (2006). Blast is damaging under tropical low land condition (Bonman et al, 1989).…”
Section: Discussionsupporting
confidence: 58%
“…Rice blast, caused by Magnaporthe oryzae is a serious disease responsible for yield loss to the tune of 80% s [2,3]. Each year, this disease is estimated to destroy enough rice that could feed more than 60 million people [4].…”
Section: Introductionmentioning
confidence: 99%